The Effectiveness of Vocabulary Mastery through the Quizlet Platform - Yusipa Sofia Aswinda; Ageung Darajat; Finny Anita (Universitas PGRI Pontianak, 2025)
This study aimed to examine the effectiveness of Quizlet in improving students’ vocabulary mastery at SMPN 03 Entikong. A quantitative approach with a pre-experimental one-group pre-test and post-test design was employed. The participants were twenty-six eighth-grade students selected through cluster random sampling. A vocabulary test consisting of spelling, usage, and meaning aspects was used as the research instrument. The data were analyzed using SPSS version 27, including descriptive statistics, Shapiro-Wilk normality test, paired sample t-test, and effect size analysis. The findings revealed that students’ vocabulary performance improved after the implementation of Quizlet. The mean score increased from 50.08 in the pre-test to 62.22 in the post-test, with a mean difference of 12.14. The normality test showed that the data were normally distributed. The paired sample t-test indicated a statistically significant difference between the two tests (t = 3.885, p < 0.001). Furthermore, the effect size value of 0.76 demonstrated that Quizlet had a strong practical impact on students’ learning outcomes. Improvements were observed in all vocabulary aspects, although usage remained the most challenging. In conclusion, Quizlet is an effective supplementary tool for enhancing students’ vocabulary mastery. Its interactive features support students’ motivation, engagement, and independent learning in English classrooms.